Legal Status Issues of Drug Abusers Following Sting Operations in Indonesia - Mohamad Adam; Puluhulawa, Fenty U.; Ismail, Dian Ekawati (Universitas Internasional Batam, 2025)
The purpose of this study is to analyze the legal status of drug abusers after a sting operation. This type of research is normative legal research with a legislative approach, case approach and conceptual approach. The analysis used in this study is qualitative data analysis through the processing of legal materials in a deductive manner. Based on the research, the results of the study show that in Law Number 35 of 2009 concerning Narcotics, it is stated that after a sting operation or after a confiscation, within a minimum of 3 x 24 hours, evidence must be tested to ensure the narcotics content found, so this can have implications for the legal status of someone arrested in a sting operation. A person caught red-handed in a narcotics case can have several possible legal statuses, including; as a witness who is arrested, if he is only at the scene without direct evidence of his involvement; as a suspect, if initial evidence is found that he has or uses narcotics; as a person without legal status who is temporarily detained, if his status is still awaiting the results of laboratory tests of evidence. Therefore, it is necessary to update the regulations through a revision of the Narcotics Law which must include a clear time limit on how someone caught red-handed must be treated before the results of the evidence test are out.